2013
DOI: 10.3389/fpls.2013.00155
|View full text |Cite
|
Sign up to set email alerts
|

Disease resistance or growth: the role of plant hormones in balancing immune responses and fitness costs

Abstract: Plant growth and response to environmental cues are largely governed by phytohormones. The plant hormones ethylene, jasmonic acid, and salicylic acid (SA) play a central role in the regulation of plant immune responses. In addition, other plant hormones, such as auxins, abscisic acid (ABA), cytokinins, gibberellins, and brassinosteroids, that have been thoroughly described to regulate plant development and growth, have recently emerged as key regulators of plant immunity. Plant hormones interact in complex net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
450
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(464 citation statements)
references
References 160 publications
(214 reference statements)
8
450
1
5
Order By: Relevance
“…5B and Dataset S1, Table S4), suggesting that the small plant line has higher basal expression levels of the defense response genes. These observations support the suggestion that there is a negative relationship between vegetative growth and defense activation (26,27), with the down-regulated defense-related gene activities associated with greater growth of the hybrids and hybrid mimic plants.…”
Section: Genes and Metabolic Pathways Important In The F1 Hybrid Phensupporting
confidence: 85%
See 1 more Smart Citation
“…5B and Dataset S1, Table S4), suggesting that the small plant line has higher basal expression levels of the defense response genes. These observations support the suggestion that there is a negative relationship between vegetative growth and defense activation (26,27), with the down-regulated defense-related gene activities associated with greater growth of the hybrids and hybrid mimic plants.…”
Section: Genes and Metabolic Pathways Important In The F1 Hybrid Phensupporting
confidence: 85%
“…The common property of genes involved in a number of the defense response pathways was their down-regulation relative to midparental values. This property fits with proposals that there is antagonism between defense response pathways and growth pathways (26,27). This counterbalancing of energy-consuming gene activities and growth is emphasized by the finding that, in small plant phenotypes, there are gene activity profiles opposite to those of the large hybrid mimics, where a number of defense response genes are up-regulated and the vegetative size of the plants is reduced.…”
Section: Genes and Metabolic Pathways Important In The F1 Hybrid Phensupporting
confidence: 84%
“…ABA is a major regulator of abiotic stress responses caused by drought, salt, cold and wounding (Christmann et al ., 2006; Raghavendra et al ., 2010), and also plays a prominent role in plant resistance to biotic stresses such as pathogen attack (Ton et al ., 2009; Denance et al ., 2013) and herbivorous insects (Bodenhausen and Reymond, 2007; Verhage et al ., 2011; Pineda et al ., 2012; Lazebnik et al ., 2014). In our study, ABA content was increased in the Arabidopsis leaves when it was inoculated with T. gamsii F18.…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of altered defense-related gene expression imply that the hybrids have a decreased basal defense response, this being more pronounced in the C24/Ler and C24/Col hybrids. Given the antagonistic relationship between plant immunity and plant growth (7,8), the lower level of defense-related metabolism could be significant for generating the greater growth of the hybrids.…”
Section: Gene Regulatory Network Involved In Defense and Stress Respmentioning
confidence: 99%
“…We found that all of the hybrids have transcription profiles implying increased stress tolerance and suppression of defense-related pathways as major altered processes, although the exact patterns of change differ between the hybrids. Given the competition between plant immunity and plant growth for resource allocation (7,8), the reduction in basal defense levels could be important for generating heterosis. Substantial changes in the auxin [indole-3-acetic acid (IAA)]-and salicylic acid…”
mentioning
confidence: 99%